Demokratisasi dalam Pendidikan: Pendidikan Berbasis Karakteristik Masyarakat Lokal - Sultoni, Agus (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2019)
Education has a clear object, namely humans. Understanding the nature of human nature, obtained an overview of the characteristics map about humans. The democratization of education can be realized, one of which is through community-based education in a national education organization. Communitybased in question is a local community with all the special characteristics it bears. By paying attention to the map of the characteristics of the local community, giving a foothold to the stakeholders to maximize the effectiveness of education - which is expected to be right on target. Schools as formalized educational institutions cannot take their roles as a whole. Two environments should not be ignored from the calculation of determining the success of students: the family environment and social environment. To achieve synergy, concrete steps must be framed in the spirit of communication and dialogue. The dialogue will open the veil of misunderstanding caused as a result of differences in thinking and perspective. The approach most relevant to this study is the socio-cultural approach. The material taught maybe a package from the institution that holds the authority of the policy, but the method of how to deliver the material is the responsibility of the Educator. The success of the packaged material is about how the Educator's method of distributing, transferring knowledge so that it can be fully accepted by students.